STRATEGI KOMUNIKASI PEMASARAN HIJAB DAN MAKANAN DAPOER KUDIL MELALUI MEDIA SOSIAL - Misroji; Nurjanah (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2023)
The This research is motivated by the fact that Dapoer Kudil uses social media to promote its products and has been proven to increase sales turnover of its products every year. Meanwhile, theoretically, the marketing communication strategy is an effort to introduce products to consumers which is very important because it relates to the success that will be obtained by sellers both through online and offline marketing. Therefore, this research formulates the problem and objectives, the communication process carried out by Dapoer Kudil in marketing its products through social media. This study uses a descriptive type of research with a qualitative approach, namely analyzing the marketing communication strategy carried out by Dapoer Kudil social media. Researchers get the data from the results of interviews, observations and documentation. The results of this study conclude that, the communication process carried out by the Dapoer Kudil social media account is a directed communication strategy, and includes a communication component. The influence of the use of social media on the marketing of Dapoer Kudil products is proven by the increase in sales turnover every year.